Transgenerational responses to heat and fasting acclimation in the Angoumois grain moth. (May 2022) - Mpofu, Precious; Cuthbert, Ross N.; Machekano, Honest; Nyamukondiwa, Casper
Abstract: Transgenerational plasticity (TGP) is a physiological mechanism where environmental experiences of parents affect phenotypes of the offspring, and potentially facilitates organisms' survival in stressful environments. The Angouimois grain moth, Sitotroga cerealella (Olivier), is a dominant primary grain pest in Africa, particularly affecting sorghum and maize staples. Despite its widely known economic significance, little is known on its thermal responses, particularly how acclimation in one generation impacts fitness in successive generations. We tested how heat (acute and dynamic) as well as fasting acclimation in one generation affects physiological tolerance (i.e., critical thermal maxima [CTmax ] and heat knock down time [HKDT]) using laboratory-reared S. cerealella populations. Specifically, we assessed whether pre-exposure to heat or fasting stress confers fitness costs or benefits in subsequent generations (i.e., through TGP). Results showed acclimation had significant effects in interaction with temperature ramping rates on CTmax . Moderate acute heat (34 °C) and dynamic temperature (28–38 °C) acclimations reduced F1 CTmax and HKDT, particularly at low ramping rates (for CTmax ). We did not find fasting acclimation to significantly affect CTmax, indicating a lack of evidence for cross tolerance and/or susceptibility. For HKDT, all acclimation treatments (including fasting) showed significantly lower HKDT compared to controls, and mostly so, for the 38 °C and dynamic acclimation (28–38 °C) treatments, indicating a transgenerational fitness cost of acclimation. This is the first report of the costs of transgenerational plasticity in a stored product pest of economic significance and has implications in designing heat-based phytosanitary grain treatments. Highlights: F1 heat acclimation significantly affected S. cerealella F2 offspring CTmax . Lower- but not higher -ramping rates significantly reduced F2 CTmax . Both F1 fasting and heat acclimation reduced F2 offspring HKDT. Dynamic heat acclimation significantly reduced heat tolerance of F2 offspring.